The double-edged sword effect of telecommuting on employees’ work engagement: evidence from China during COVID-19 - Ma, Lu; Zheng, Yunjian; Wei, Ye (Frontiers in Psychology, 2023)
Purpose - Building on the Job Demands-Resources (JD-R) model, this study aims to explore how telecommuting affects employee’ work engagement, and consider how perceived supervisor support moderates this effect. Design/methodology/approach - A time-lagged study was conducted on 286 employees from four enterprises in southern China. Findings - The results showed that telecommuting both decreased work engagement by triggering work-family conflict and enhanced work engagement by increasing job autonomy. In addition, perceived supervisor support enhanced the positive direct effect of telecommuting on job autonomy and the indirect effect on employee’ work engagement, while perceived supervisor support weakened the negative direct effect of telecommuting on work-family conflict and the indirect effect on employee’ work engagement. Originality/value - This study enrich the literature on telecommuting and employee engagement, and emphasize the importance of perceived supervisor support in this context. Additionally, this study provides some practical implications for companies to adapt and manage telecommuting.